ENVIRONMENTAL CHANGE AND THE CHALLENGES OF TOURISM PATRONAGE IN THE OBUDU RANCH RESORT NIGERIA - UTANG, Pius B.; ADIE, Lydia A. (Journal of Environmental Management and Tourism, 2011)
Spatial reorganization in the Obudu Ranch has been massive since the last decade and this meant accelerated changes to the biophysical milieu. This study sought to examine the reorganizational outcomes and changes in the biophysical attractions as they relate to visitation (patronage). Patronage pattern was examined; observed spatial changes highlighted; specific attractions and the observed changes identified; and relationship between environmental change and patronage established. Data on vegetation change, patronage and physical infrastructure development in temporal context were used. Also obtained was data on specific attractions and observed physical changes by respondents. Geographic analysis was based on thematic maps, while statistical analyses were descriptive (including percentages, column and line graphs) and inferential statistics (time series, using least square regression, and chi square) were employed. Findings indicated that tourism, particularly international visitation, to the ranch followed a declining trend during the ten years of data, and this trend or change was significant over time. Environmental changes appear to influence patronage as reported by the tourists and indigenous population, while no difference existed between the tourist providers, tourists and local population on the relationship between environmental change and tourism patronage. Deemphasizing further expansion and encouragement of public mass transport and the cable car were some of the recommendations. Also recommended were education on energy efficiency and less dependence on fuel wood, which triggers deforestation.